Pelatihan untuk Mengetahui Apakah Self-Regulated Learning dapat Meningkatkan Akademik Self-Efficacy - Denata, Intan; Tesa Anggraini; Rafika Febrilla (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Low self-confidence among students regarding their academic abilities has an impact on suboptimal learning outcomes. This problem is related to students' weak ability to regulate their own learning process, or self-regulated learning (SRL). The purpose of this study was to determine whether self-regulated learning training could improve students' academic self-efficacy. This study used an experimental method with a pretest-posttest design. The research subjects were 30 students from Campus V Bukittinggi who were selected using simple random sampling. The instruments used were the self-regulated learning scale and the self-efficacy scale, with data analysis using a paired sample t-test through the SPSS program. The results showed a significant difference between the pretest and posttest scores in the aspects of knowledge, attitude, and independent learning behavior (t = 10.67; p < 0.05), which means that self-regulated learning training is effective in improving students' academic self-efficacy. In conclusion, the ability to regulate oneself in learning plays an important role in building individual academic confidence. The implications of this study emphasize the importance of implementing self-regulated learning training in educational environments to improve students' learning competence and academic confidence.